Huge Retroperitoneal Cyst Masquerading as Ovarian Tumour: A Case Report - Johan, Syamim; Hassan, Muhammad Firdaus; Hayati, Firdaus; Azizan, Nornazirah; Payus, Alvin Oliver; Edwin See, Un Hean (Frontiers in Surgery, 2020)
Retroperitoneal cystic mass is a rare surgical condition that is often misdiagnosed preoperatively. Here, we report a case of a 56-year-old woman who presented with an abdominal swelling for one-year duration which was associated with lower abdominal pain for six months. Her abdominal radiograph showed a huge radiopaque lesion, and contrastenhanced computed tomography scan of the abdomen was reported as left ovarian serous cystadenoma causing local mass effect to the left ureter leading to mild left hydronephrosis. She underwent exploratory laparotomy and noted there was a huge retroperitoneal cystic mass. The histopathological assessment finding was consistent with a benign retroperitoneal cyst. This case report aims to share the rare case of primary retroperitoneal lesions which can cause a diagnostic challenge preoperatively to all clinician despite advance achievement in medical imaging.